HUBUNGAN ANTAR MANUSIA PEGAWAI DINAS PENDIDIKAN KOTA PAYAKUMBUH - Andre Tane (Jurnal Bahana Manajemen Pendidikan, 2015)
The goal of this research is to provide information about Human relations of employees in the education office payakumbuh city. Human Relations of employees seen from 1) Mutual Respect, 2)Loyalty, 3) Cooperation, 4) Familiarity. The population in this research is 85 employees. Determination of the number samples by looking at Table Krejcie. Based on the Table Krejcie is 73 sample of employees. The Instruments used to collect data in this research is questionnaire Likert scale models that have been tested and the results are valid and reliable. Research data processing performed by using the average formula (mean). In general, the results of this research is Human Relations of employees in education office payakumbuh is good with an average score of 3,6. Key Words: Human Relations, Employees